Mayapuri Radiological Catastrophe: Good Practices and the Lessons Learnt - Sharma, Sandeep; Sharma, Rakesh K.; Singh, Rajesh Kumar (Current Radiopharmaceuticals, 2022)
Background: Advances in the peaceful applications of ionizing radiation have brought in its wake the inevitable concern about radioactivity. Almost a decade ago, an infamous unprecedented radiological exposure incident occurred in Delhi, which has not only some positive aspects for imbibing good practices to emulate but also lessons learnt to further improvise the overall management, respectively. Objective: The Mayapuri incident at Delhi exposed the lack of awareness and laxity on the part of University of Delhi authorities in disposing of the Cobalt Irradiator, and the further insecure handling of the orphan radioactive source. Since an occurrence like this was unparalleled, it was necessary to flag all interlinked issues and put in place a technology management system that should address them. Methods: The methodology includes an in-depth discussion about the good practices and lessons learnt of the then-existing techno-legal systems and the response mechanism to the Mayapuri radiological incident from various departments of repute, both governmental as well as non-governmental. Result and Conclusion: The present article attempts to intensify pragmatic approaches to proactively avert and thwart ‘orphan source’ incidents like the Mayapuri radiological incident, so that threat to the society is minimal, and putting in place enhanced medical preparedness measures for the management of radiation casualties caused by ignorance, negligence, incompetence, accident, or malicious intention.
Keywords: radiation